Optimizing the noninvasive ventilation pathway for patients with amyotrophic lateral sclerosis/motor neuron disease: a systematic review. Issue 7 (2nd October 2019) - Baxter, Susan Kathryn; Johnson, Maxine; Clowes, Mark; O'Brien, David; Norman, Paul; Stavroulakis, Theocharis; Bianchi, Stephen; Elliott, Mark; McDermott, Christopher; Hobson, Esther
Abstract: Objective : To systematically review quantitative and qualitative literature on optimal provision of noninvasive ventilation (NIV) for patients with amyotrophic lateral sclerosis/motor neuron disease (MND). Methods : A systematic search of electronic databases, together with supplementary search methods was used to identify relevant literature from the last 20 years. Studies of any empirical design with an English abstract were eligible for inclusion. Data from documents meeting our criteria were extracted and synthesized using narrative and thematic synthesis. A patient pathway of care model was used to integrate data and provide a process perspective to the findings. Results : While the importance of individualizing care was highlighted, factors optimizing use for all patients include: specialized multi-disciplinary team service provision; determining need using respiratory function tests in addition to symptom report; providing adequate information for patients and their family; paying attention to the role of carers in decision-making; adequately managing secretions; considering the most advantageous place of initiation; optimizing the interface, machine mode, and settings for patient comfort and effectiveness; providing supportive interventions where appropriate; regular monitoring and adjustment of settings; and providing opportunities for ongoing discussion of patient wishes. Conclusions : Optimizing use of NIV in people with MND requires consideration of multiple factors as part of a process throughout the patient pathway. Current guidelines predominantly focus on the initiation of NIV and may underplay psychosocial factors. We have made evidence-based recommendations for each step in the pathway, which may help improve optimal uptake, usage, quality of life, and survival outcomes in patients with MND.